Capacitor packaging material, preparation method and application thereof, and capacitor packaging method

By using specific coupling agent modified silica, rubber toughener, modified anhydride and epoxy modified acrylic resin in capacitance materials, the problems of high linear expansion coefficient, poor toughness and poor adhesion of the capacitor packaging materials are solved, and the low expansion coefficient, high toughness and good adhesion of the material are achieved, and the stability of the capacitor performance is improved.

CN119709074APending Publication Date: 2025-03-28XIAMEN YIFANDA NEW MATERIAL CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411965923.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing capacitor packaging materials have a high linear expansion coefficient, poor toughness, and poor adhesion to ceramic interfaces, resulting in unstable capacitance performance.

Method used

Silica, rubber toughener, modified anhydride and epoxy modified acrylic resins are used to form resin components, cured components and adhesive components of capacitive packaging materials, which work together to reduce the linear expansion coefficient and improve toughness and improve the adhesion between ceramics and packaging materials.

Benefits of technology

The linear expansion coefficient of the capacitive packaging material is significantly reduced, its toughness is improved, and the adhesion with the ceramic interface is improved, cracking and gaps occur after curing, and the protection effect of the capacitance is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218345630000131
    Figure BDA0005218345630000131
  • Figure BDA0005218345630000141
    Figure BDA0005218345630000141
Patent Text Reader

Abstract

The invention belongs to the technical field of capacitor materials, and particularly relates to a capacitor packaging material, a preparation method and application thereof and a capacitor packaging method. The capacitor packaging material comprises a resin component A, a curing component B and a bonding component C, the resin component A contains bisphenol A epoxy resin I, polyether polyol I and optional rubber toughening agent I and modified silicon dioxide I; the curing component B contains anhydride and optional rubber toughening agent II and modified silicon dioxide II; the bonding component C contains epoxy modified acrylic resin and bisphenol A epoxy resin II. The key point of the capacitor packaging material is that the specific coupling agent modified silicon dioxide, the rubber flexibilizer, the modified anhydride and the epoxy modified acrylic resin are introduced into the capacitor packaging material, and all the components cooperate with one another to play a synergistic role, so that the capacitor packaging material has a relatively low linear expansion coefficient and relatively high toughness; the cured packaging material is free of cracking, and the contact surface between the packaging material and the ceramic is well combined without gaps.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of capacitor materials, and in particular relates to a capacitor packaging material and a preparation method and application thereof, as well as a capacitor packaging method. Background Art

[0002] Capacitors are one of the electronic components used in large quantities in electronic equipment. They are widely used in DC isolation, coupling, bypass, filtering, tuning circuits, energy conversion, control circuits, etc. The main body of the capacitor is ceramic material, and must be encapsulated with epoxy resin. If the high-voltage ceramic capacitor is not encapsulated with epoxy resin, it will cause the ceramic capacitor to directly contact the air, which will directly affect the capacity and capacitive reactance of the capacitor. In other words, if the ceramic capacitor is exposed to air, its capacity will become lower, and even the high-voltage ceramic capacitor may change from the original 2000PF high-voltage ceramic capacitor to a capacitor of only a few hundred PF. In addition, if the ceramic capacitor is exposed to air, its capacitive reactance will also decrease, and as the resistance value and capacity become smaller and smaller, the performance of the ceramic capacitor will be lost.

[0003] However, due to the large difference in linear expansion coefficients between ceramics and epoxy resins, the ceramic interface and epoxy resin have poor adhesion, and gaps are likely to appear on the contact surface of ceramics and epoxy resins or cracks on the surface of the packaging material after curing, which will lead to unstable performance of the produced capacitors, prone to cracking and performance degradation. At present, most domestic manufacturers use the method of adding fillers to reduce the linear expansion coefficient of the system, but the addition of fillers will increase the viscosity of the entire system, deteriorate the processability of the material, and also reduce the toughness of the system, and the improvement of the adhesion between ceramics and epoxy resins is limited. Summary of the invention

[0004] One of the purposes of the present invention is to provide a capacitor packaging material with a low linear expansion coefficient and high toughness after curing, so as to address the problems of existing capacitor packaging materials having a high linear expansion coefficient, poor toughness and poor adhesion to the ceramic interface, thereby significantly improving the adhesion between the ceramic and the packaging material.

[0005] Specifically, the capacitor packaging material comprises a resin component A, a curing component B and an adhesive component C; the resin component A contains bisphenol A epoxy resin I, polyether polyol I and optional rubber toughening agent I and modified silica I; the curing component B contains anhydride and optional rubber toughening agent II and modified silica II; the resin component A contains rubber toughening agent I and / or the curing component B contains rubber toughening agent II, the resin component A contains modified silica I and / or the curing component B contains modified silica II; the adhesive component C contains epoxy modified acrylic resin, bisphenol A epoxy resin II and optional surface additives and diluents; the modified silicon dioxide I and modified silicon dioxide II are independently obtained by modifying silicon dioxide with a silane coupling agent and an aluminate coupling agent; the acid anhydride includes modified acid anhydride and optional unmodified acid anhydride; the modified acid anhydride is obtained by esterification reaction of polyether polyol II and unmodified acid anhydride in the presence of a catalyst; the epoxy-modified acrylic resin is obtained by polymerization reaction of acrylic acid, hydroxy acrylate compounds, acrylate compounds and bisphenol A epoxy resin III in the presence of an initiator.

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned capacitor packaging material, which comprises: mixing bisphenol A epoxy resin I, polyether polyol I, and optional rubber toughening agent I and modified silica I to obtain resin component A; mixing acid anhydride and optional rubber toughening agent II and modified silica II to obtain curing component B; and mixing epoxy-modified acrylic resin, bisphenol A epoxy resin II, and optional surface additives and diluents to obtain bonding component C.

[0007] A third object of the present invention is to provide an application of the above capacitor packaging material in capacitor devices with packaging requirements.

[0008] The fourth object of the present invention is to provide a capacitor packaging method, which comprises: coating the adhesive component C of the capacitor packaging material on the surface of the capacitor material to form an adhesive layer, and then mixing the resin component A and the curing component B of the capacitor packaging material and coating them on the surface of the adhesive layer, and completing the capacitor packaging after curing.

[0009] The key to the present invention is to introduce silica modified by a specific coupling agent, a rubber toughening agent, a modified acid anhydride and an epoxy-modified acrylic resin into the capacitor packaging material, and the various components cooperate with each other to play a synergistic role, so that the capacitor packaging material has a lower linear expansion coefficient that matches the ceramic material and a higher toughness, and improves the adhesion with the ceramic material. The cured packaging material has no cracks and the contact surface between the packaging material and the ceramic is well bonded and has no gaps, which is conducive to the protective effect of the packaging material on the capacitor. The reasons are speculated to be: using specific silane coupling agents and aluminate coupling agents to coat and modify silica, reducing the effect of silica on the viscosity of the packaging material system, improving the processability of the packaging material and the amount of silica filler used, thereby reducing the linear expansion coefficient of the packaging material, and also helping to improve the mechanical properties (toughness) of the system, thereby improving the adhesion between the capacitor packaging material and the ceramic interface; introducing epoxy-modified acrylic resin as an adhesive component, first forming an adhesive layer containing epoxy groups and unsaturated double bonds on the surface of the ceramic material, the adhesive layer not only has a good bonding force with the surface of the ceramic material, but also can react with the resin component and the curing component in the packaging material to enhance the bonding force, thereby improving the adhesion between the ceramic material and the packaging material; the rubber toughening agent and the modified acid anhydride cooperate with each other to improve the toughness of the packaging material and its crack resistance to better match the ceramic material, thereby helping to improve the adhesion between the packaging material and the ceramic material. DETAILED DESCRIPTION

[0010] The capacitor packaging material provided by the present invention comprises a resin component A, a curing component B and an adhesive component C. The resin component A contains bisphenol A epoxy resin I, polyether polyol I and optional rubber toughening agent I and modified silicon dioxide I. The curing component B contains anhydride and optional rubber toughening agent II and modified silicon dioxide II. The adhesive component C contains epoxy-modified acrylic resin, bisphenol A epoxy resin II and optional surface additives and diluents. The resin component A contains rubber toughening agent I and / or the curing component B contains rubber toughening agent II, and the resin component A contains modified silicon dioxide I and / or the curing component B contains modified silicon dioxide II. That is, the resin component A may contain rubber toughening agent I and the curing component B may not contain rubber toughening agent II, or the curing component B may contain rubber toughening agent II and the resin component A may not contain rubber toughening agent I, or the resin component A may contain rubber toughening agent I and the curing component B may contain modified silica II, but the resin component A may not contain rubber toughening agent I and the curing component B may not contain rubber toughening agent II. The resin component A may contain modified silica I and the curing component B may not contain modified silica II, or the curing component B may contain modified silica II and the resin component A may not contain modified silica I, or the resin component A may contain modified silica I and the curing component B may contain modified silica II, but the resin component A may not contain modified silica I and the curing component B may not contain modified silica II.

[0011] In the present invention, based on the total mass of the resin component A and the curing component B, the content of the bisphenol A epoxy resin I is preferably 10 to 20 wt%, such as 10 wt%, 12 wt%, 15 wt%, 18 wt%, 20 wt% or any value therebetween; the content of the polyether polyol I is preferably 0.5 to 2.5 wt%, such as 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt% or any value therebetween; the content of the acid anhydride is preferably 10 to 20 wt%, such as 10 wt%, 12 wt%, , 15wt%, 18wt%, 20wt% or any value therebetween; the total content of the rubber toughening agent I and the rubber toughening agent II is preferably 1-5wt%, such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value therebetween; the total content of the modified silica and modified silica II is preferably 50-79wt%, such as 50wt%, 52.5wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 78wt%, 79wt% or any value therebetween.

[0012] In a specific embodiment, based on the total mass of the resin component A, the content of the bisphenol A epoxy resin I is preferably 20-40wt%, such as 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or any value therebetween; the content of the polyether polyol I is preferably 1-5wt%, such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value therebetween; the content of the rubber toughening agent I is preferably 1-5wt%, such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value therebetween; the content of the modified silica I is preferably 50-78wt%, such as 50wt%, 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 78wt% or any value therebetween.

[0013] In a specific embodiment, based on the total mass of the curing component B, the content of the acid anhydride is preferably 20-40wt%, such as 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or any value therebetween; the content of the rubber toughening agent II is preferably 1-5wt%, such as 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value therebetween; the content of the modified silica II is preferably 55-79wt%, such as 55wt%, 60wt%, 65wt%, 70wt%, 75wt%, 79wt% or any value therebetween.

[0014] In a specific embodiment, based on the total mass of the adhesive component C, the content of the epoxy-modified acrylic resin is preferably 40-60wt%, such as 40wt%, 45wt%, 50wt%, 55wt%, 60wt% or any value therebetween; the content of the bisphenol A epoxy resin II is preferably 10-30wt%, such as 10wt%, 15wt%, 20wt%, 25wt%, 30wt% or any value therebetween; the content of the surface additive is preferably 0-5wt%, such as 0wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value therebetween; the content of the diluent is preferably 0-45wt%, such as 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or any value therebetween.

[0015] In the present invention, the mass ratio of the resin component A to the curing component B is preferably 100:(80-120), such as 100:80, 100:90, 100:100, 100:110, 100:120 or any value therebetween, which is more conducive to the full curing of the material during use. Taking the mass of the resin component A as 100 parts by weight, the mass of the curing component B is preferably 80-120 parts by weight, such as 80, 85, 90, 95, 100, 105, 110, 115, 120 parts by weight or any value therebetween. The amount of the adhesive component C used depends on the size of the capacitor, and is based on coating the entire surface of the capacitor.

[0016] In the present invention, the bisphenol A epoxy resin I, bisphenol A epoxy resin II and bisphenol A epoxy resin III are each independently selected from one of E20, E44, E51 and E54.

[0017] In the present invention, the polyether polyol I and the polyether polyol II are independently selected from at least one of polytetramethylene glycol, polyethylene glycol, polypropylene glycol, polyoxypropylene glycol and polyoxypropylene triol.

[0018] In the present invention, the number average molecular weight Mn of the polyether polyol I and the polyether polyol II is preferably independently 200-1000 g / mol, such as 200 g / mol, 300 g / mol, 500 g / mol, 800 g / mol, 1000 g / mol or any value therebetween.

[0019] In the present invention, the rubber toughening agent I and the rubber toughening agent II are each independently selected from at least one of carboxyl liquid nitrile rubber, hydroxyl-terminated liquid nitrile rubber, polysulfide rubber, liquid silicone rubber, and ABS.

[0020] In the present invention, the modified silica I and modified silica II are independently obtained by modifying silica with a silane coupling agent and an aluminate coupling agent.

[0021] Further, the mass ratio of the silane coupling agent to the aluminate coupling agent is preferably (1-2):1, such as 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1 or any value therebetween, which is more conducive to improving the compatibility of the modified silica with the system. The mass ratio of the sum of the mass of the silane coupling agent and the aluminate coupling agent to the silica is preferably (0.02-0.05):1, such as 0.02:1, 0.03:1, 0.04:1, 0.05:1 or any value therebetween. The silica can be spherical and / or quasi-spherical particles, preferably spherical silica.

[0022] Furthermore, the conditions of the modification reaction may include: the temperature is preferably 100-140°C, such as 100°C, 110°C, 120°C, 130°C, 140°C; the time is preferably 4-6h, such as 4h, 4.5h, 5h, 5.5h, 6h or any value therebetween.

[0023] In a specific embodiment, the preparation method of the modified silica I or modified silica II can be as follows: a silane coupling agent and an aluminate coupling agent are first mixed to obtain a modified mixed solution, and then the modified mixed solution is sprayed while stirring the silica so that the coupling agent is evenly coated on the surface of the silica, and then the material is treated at 100 to 140° C. for 4 to 6 hours to obtain modified silica I or modified silica II.

[0024] Further, the silane coupling agent is preferably at least one selected from aminosilane, mercaptosilane, and epoxysilane, and its specific examples can be conventionally selected in the prior art. The aluminate coupling agent is preferably at least one selected from SG-Al821 (distearoyloxyisopropylaluminate), DL-411, DL-411AF, DL-411D, and DL-411DF.

[0025] In the present invention, the acid anhydride includes modified acid anhydride and optionally unmodified acid anhydride.

[0026] Furthermore, in the preparation process of the modified acid anhydride, the mass ratio of the modified acid anhydride to the unmodified acid anhydride is preferably 1:(0.3-0.5), such as 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5 or any value therebetween, which is more conducive to improving the toughness of the packaging material to meet the toughness requirements of the capacitor product.

[0027] In the present invention, the modified acid anhydride is obtained by esterifying polyether polyol II with unmodified acid anhydride in the presence of a catalyst.

[0028] Furthermore, the mass ratio of the polyether polyol II, the unmodified acid anhydride and the catalyst is preferably (1.5-2.5):1:(0.01-0.03). Taking the mass of the unmodified acid anhydride as 1 part by weight, the mass of the polyether polyol II is preferably 1.5-2.5 parts by weight, such as 1.5, 1.8, 2, 2.2, 2.5 parts by weight or any value therebetween; the mass of the catalyst is preferably 0.01-0.03 parts by weight, such as 0.01, 0.015, 0.02, 0.025, 0.03 parts by weight or any value therebetween.

[0029] Furthermore, the conditions of the esterification reaction may include: the temperature is preferably 130-160°C, such as 130°C, 140°C, 150°C, 160°C or any value therebetween; the time is preferably such that the difference in the anhydride content of the reaction system is within 10% within 2 hours.

[0030] In a specific embodiment, the preparation method of the modified acid anhydride can be as follows: after mixing polyether polyol II, unmodified acid anhydride and catalyst, continuously carry out esterification reaction at 130-160°C, test the anhydride content of the reaction system every 0.5h after 3h, and stop the reaction when the difference of the anhydride content of the reaction system is within 10% within 2h, and the obtained product is the modified acid anhydride.

[0031] Furthermore, the unmodified acid anhydride is preferably at least one selected from tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylnadic anhydride, and dodecylsuccinic anhydride.

[0032] Furthermore, the catalyst is preferably at least one selected from tetrabutylammonium bromide, benzyltriethylammonium chloride, and boron trichloride zinc alkyl tertiary amine.

[0033] In the present invention, the epoxy-modified acrylic resin is obtained by polymerizing acrylic acid, hydroxy acrylic ester compounds, acrylic ester compounds and bisphenol A epoxy resin III in the presence of an initiator.

[0034] In a specific embodiment, the preparation method of the epoxy-modified acrylic resin preferably includes the following steps: subjecting bisphenol A epoxy resin III to a ring-opening addition reaction with acrylic acid, and subjecting the obtained intermediate product to a polymerization reaction with a hydroxy acrylate compound and an acrylate compound in the presence of an initiator, and the obtained product is an epoxy-modified acrylic resin.

[0035] Furthermore, the molar ratio of the bisphenol A epoxy resin III to acrylic acid is preferably (1-1.2):1, such as 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1 or any value therebetween.

[0036] Furthermore, the molar ratio of the acrylic acid to the hydroxy acrylate compound and the acrylate compound is preferably 1:(1.5-4):(0.5-1.5), which is more conducive to improving the adhesion of the adhesive. Based on the amount of the acrylic acid as 1 mol, the amount of the hydroxy acrylate compound is preferably 1.5-4 mol, such as 1.5 mol, 2 mol, 2.5 mol, 3 mol, 3.5 mol, 4 mol or any value therebetween; the amount of the acrylate compound is preferably 0.5-1.5 mol, such as 0.5 mol, 0.8 mol, 1 mol, 1.2 mol, 1.5 mol or any value therebetween.

[0037] Furthermore, the conditions for the ring-opening addition may include: the temperature is preferably 70-90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; the time is preferably 1-3h, such as 1h, 1.5h, 2h, 2.5h, 3h or any value therebetween.

[0038] Furthermore, the conditions of the polymerization reaction may include: the temperature is preferably 70-90°C, such as 70°C, 75°C, 80°C, 85°C, 90°C or any value therebetween; the time is preferably 2-3h, such as 1h, 1.5h, 2h, 2.5h, 3h or any value therebetween.

[0039] Furthermore, the hydroxyacrylate compound is preferably at least one selected from hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate.

[0040] Furthermore, the acrylic acid ester compound is preferably at least one selected from methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate and butyl methacrylate.

[0041] Furthermore, the initiator is selected from at least one of benzoyl peroxide, 3,5,5-trimethylhexanoic acid tert-butyl peroxide, and di-tert-butyl peroxide.

[0042] The preparation method of the capacitor packaging material provided by the present invention comprises: mixing bisphenol A epoxy resin I, polyether polyol I, and optional rubber toughening agent I and modified silicon dioxide I to obtain resin component A; mixing acid anhydride, optional rubber toughening agent II and modified silicon dioxide II to obtain curing component B; and mixing epoxy-modified acrylic resin, bisphenol A epoxy resin II, and optional surface additives and diluents to obtain bonding component C.

[0043] In a specific embodiment, the preparation method of the capacitor packaging material specifically comprises the following steps: bisphenol A epoxy resin I, polyether polyol I and rubber toughening agent I are first stirred and mixed for 0.5 to 1 hour at a stirring speed of 400 to 600 rpm, and then modified silicon dioxide I is added and stirred and mixed for 0.5 to 1 hour under vacuum conditions, the vacuum degree is 200 to 300 Pa, and the stirring speed is 700 to 900 rpm, and the resulting mixture is the resin component A; anhydride (modified anhydride and optional The unmodified acid anhydride) and rubber toughener II are first stirred and mixed for 0.5 to 1 hour at a stirring speed of 200 to 400 rpm, and then modified silica II is added and continued to be stirred and mixed for 0.5 to 1 hour under vacuum conditions, with a vacuum degree of 200 to 300 Pa and a stirring speed of 700 to 900 rpm. The resulting mixture is the curing component B; the epoxy-modified acrylic resin, bisphenol A epoxy resin II and optional surface additives and diluents are mixed and stirred for 0.5 to 1 hour, and the resulting mixture is the adhesive component C.

[0044] Furthermore, the surface additive may be a conventional choice in the art, and specific examples thereof include but are not limited to: at least one of a defoaming agent, a wetting and dispersing agent, and a leveling agent.

[0045] Furthermore, the diluent may be a conventional choice in the art, and specific examples thereof include but are not limited to: at least one of xylene, ethyl acetate, and butyl acetate.

[0046] The capacitor packaging method provided by the present invention comprises: coating the adhesive component C of the capacitor packaging material on the surface of the capacitor material to form an adhesive layer, then mixing the resin component A and the curing component of the capacitor packaging material and coating them on the surface of the adhesive layer, and completing the capacitor packaging after curing.

[0047] In a specific embodiment, the capacitor packaging method specifically includes the following steps: coating the adhesive component C of the capacitor packaging material on the surface of the capacitor material, placing the ceramic in a mold, and then mixing the resin component A and the curing component B of the capacitor packaging material in a certain mass ratio, pouring the mixture into the mold for packaging, and then placing the mold at 110 to 130° C. for curing for 10 to 15 hours, thereby completing the capacitor packaging.

[0048] In addition, the terms "Ⅰ", "Ⅱ" and "Ⅲ" are only for the purpose of convenience of description and cannot be interpreted as special limitations on the type and quantity of technical features.

[0049] The present invention will be described in detail below through specific embodiments.

[0050] Sources of raw materials in the following examples and comparative examples: polyether polyol, purchased from Guangzhou Fengtian Chemical Co., Ltd., brand PEG400, Mn = 400 g / mol; polyether polyol, purchased from Jurong Ningwu New Materials Co., Ltd., brand NJ-204, Mn = 204 g / mol; bisphenol A epoxy resin E20, purchased from Nanya Electronic Materials (Kunshan) Co., Ltd., brand NPES-901; bisphenol A epoxy resin E51, purchased from Nanya Electronic Materials (Kunshan) Co., Ltd., brand NPEL-128E.

[0051] Preparation Example 1 Preparation of modified silicon dioxide

[0052] The silane coupling agent (3-(2,3-epoxypropoxy)propyltrimethoxysilane) and the aluminate coupling agent DL-411 were mixed in a mass ratio of 1:1 to obtain 36 g of a modified mixed solution. Then, the spherical silica (1000 g) was stirred and sprayed with the modified mixed solution so that the coupling agent was evenly coated on the surface of the spherical silica. The material was then baked at 120°C for 5 hours to obtain modified spherical silica a-1.

[0053] Preparation Example 2 Preparation of modified silicon dioxide

[0054] The silane coupling agent (3-(2,3-epoxypropoxy)propyltrimethoxysilane) and the aluminate coupling agent DL-411 were mixed in a mass ratio of 2:1 to obtain 36 g of a modified mixed solution. Then, the spherical silica (1000 g) was stirred and sprayed with the modified mixed solution so that the coupling agent was evenly coated on the surface of the spherical silica. The material was then baked at 120°C for 5 hours to obtain modified spherical silica a-2.

[0055] Preparation Example 3

[0056] Polyether polyol PEG400, tetrahydrophthalic anhydride and catalyst - tetrabutylammonium bromide are mixed in a mass ratio of 2:1:0.02, and the esterification reaction is continuously carried out at 145°C. After 3 hours, the anhydride content of the reaction system is tested every 0.5 hours until the difference in the anhydride content of the reaction system is within 10% within 2 hours. The reaction is stopped, and 50% of the total mass of the mixture is added with methyltetrahydrophthalic anhydride. The resulting product is a mixed anhydride I containing modified anhydride b-1 and methyltetrahydrophthalic anhydride.

[0057] Preparation Example 4

[0058] Polyether polyol NJ-204, hexahydrophthalic anhydride and catalyst - tetrabutylammonium bromide are mixed in a mass ratio of 2:1:0.02, and the esterification reaction is continuously carried out at 145°C. After 3 hours, the anhydride content of the reaction system is tested every 0.5 hours. The reaction is stopped when the difference in the anhydride content of the reaction system is within 10% within 2 hours. Methyltetrahydrophthalic anhydride in an amount of 50% of the total mass of the mixture is added, and the resulting product is a mixed anhydride II containing modified anhydride b-2 and methyltetrahydrophthalic anhydride.

[0059] Preparation Example 5 Preparation of epoxy-modified acrylic resin

[0060] In a four-necked flask equipped with a stirrer, a reflux condenser and a thermometer, add 1 mol of bisphenol A epoxy resin E20 (NPES-901) and 200 mL of xylene, stir and heat to 80°C, then add 1 mol of acrylic acid dropwise, and after all the addition is completed, time the reaction for 2 hours; mix and dissolve 1 mol of methyl methacrylate, 2 mol of hydroxypropyl acrylate and 10 g of benzoyl peroxide, add the mixture dropwise into the above reaction flask and continue to react at 80°C for 2 hours. After evaporating the solvent, the product obtained is epoxy-modified acrylic resin c-1.

[0061] Preparation Example 6 Preparation of epoxy-modified acrylic resin

[0062] In a four-necked flask equipped with a stirrer, a reflux condenser and a thermometer, add 1 mol of bisphenol A epoxy resin E51 (NPEL-128E) and 200 mL of xylene, stir and heat to 80°C, then add 1 mol of acrylic acid dropwise, and after all the addition is completed, time the reaction for 2 hours; mix and dissolve 1 mol of ethyl methacrylate, 2 mol of hydroxyethyl acrylate and 10 g of benzoyl peroxide, add the mixture dropwise into the above reaction flask and continue to react at 80°C for 2 hours. After evaporating the solvent, the product obtained is epoxy-modified acrylic resin c-2.

[0063] Comparative Preparation Example 1

[0064] A reference spherical silica was prepared according to the method of Preparation Example 1, except that the same mass of silane coupling agent (3-(2,3-epoxypropoxy)propyltrimethoxysilane) was used instead of the aluminate coupling agent DL-411, and the other conditions were the same as those in Preparation Example 1, thereby preparing a reference spherical silica da-1.

[0065] Comparative Preparation Example 2

[0066] Reference spherical silica was prepared according to the method of Preparation Example 1, except that the same mass of aluminate coupling agent DL-411 was used instead of the silane coupling agent (3-(2,3-epoxypropoxy)propyltrimethoxysilane), and the other conditions were the same as those in Preparation Example 1, thereby preparing reference spherical silica da-2.

[0067] Example 1

[0068] 36g of bisphenol A epoxy resin (10g of E20 (NPES-901) and 26g of E51 (NPEL-128E)), 2g of polyether polyol PEG400, and 2g of carboxyl liquid nitrile rubber were first mixed and stirred for 0.5h at a stirring speed of 500rpm, and then 60g of modified spherical silica a-1 was added and stirred for 0.5h while evacuating the mixture at a vacuum degree of 200Pa and a stirring speed of 800rpm. After the stirring was completed, the resulting mixture was the resin component A;

[0069] 28g of the mixed anhydride I obtained in Preparation Example 3 and 2g of carboxyl liquid nitrile rubber were stirred for 0.5h at a stirring speed of 300rpm, and then 70g of modified spherical silica a-1 was added and stirred for 0.5h while evacuating the mixture at a vacuum degree of 200Pa and a stirring speed of 800rpm. After the stirring was completed, the resulting mixture was the curing component B;

[0070] 50 g of epoxy-modified acrylic resin c-1, 20 g of bisphenol A epoxy resin E20 (NPES-901), 1.5 g of surface additive (organic silicone leveling agent BYK306) and 28.5 g of xylene were mixed and stirred for 0.5 h. The mixture obtained after the stirring was completed was the adhesive component C.

[0071] Example 2

[0072] 24g of bisphenol A epoxy resin E51 (NPEL-128E), 5g of polyether polyol NJ-204, and 1g of hydroxyl-terminated liquid nitrile rubber were first mixed and stirred for 0.5h at a stirring speed of 500rpm, and then 70g of modified spherical silica a-2 was added and stirred for 0.5h while evacuating the mixture at a vacuum degree of 200Pa and a stirring speed of 800rpm. After the stirring was completed, the resulting mixture was the resin component A;

[0073] 25g of the mixed anhydride II obtained in Preparation Example 4 and 4g of the hydroxyl-terminated liquid nitrile rubber were stirred for 0.5h at a stirring speed of 300rpm, and then 71g of the modified spherical silica a-2 was added and stirred for 0.5h while evacuating the mixture at a vacuum degree of 200Pa and a stirring speed of 800rpm. After the stirring was completed, the resulting mixture was the curing component B;

[0074] 50 g of epoxy-modified acrylic resin c-2, 20 g of bisphenol A epoxy resin E51 (NPEL-128E), 1.5 g of surface additive (organic silicone leveling agent BYK306) and 28.5 g of xylene were mixed and stirred for 0.5 h. The mixture obtained after the stirring was completed was the adhesive component C.

[0075] Example 3

[0076] 28g of bisphenol A epoxy resin E51 (NPEL-128E), 1g of polyether polyol, and 4g of hydroxyl-terminated liquid nitrile rubber were first mixed and stirred for 0.5h at a stirring speed of 500rpm, and then 57g of modified spherical silica a-2 was added and stirred for 0.5h while evacuating the mixture at a vacuum degree of 200Pa and a stirring speed of 800rpm. After the stirring was completed, the resulting mixture was the resin component A;

[0077] 25 g of the mixed anhydride I obtained in Preparation Example 3 and 2 g of the hydroxyl-terminated liquid nitrile rubber were stirred for 0.5 h at a stirring speed of 300 rpm, and then 78 g of the modified spherical silica a-2 was added and stirred for 0.5 h while evacuating the mixture at a vacuum degree of 200 Pa and a stirring speed of 800 rpm. After the stirring was completed, the resulting mixture was the curing component B;

[0078] 50 g of epoxy-modified acrylic resin c-2, 20 g of bisphenol A epoxy resin E51 (NPEL-128E), 1.5 g of surface additive (organic silicone leveling agent BYK306) and 28.5 g of xylene were mixed and stirred for 0.5 h. The mixture obtained after the stirring was completed was the adhesive component C.

[0079] Example 4

[0080] The capacitor packaging material was prepared according to the method of Example 1, except that the modified anhydride b-1 of the same mass was used instead of the mixed anhydride I, and the other conditions were the same as those of Example 1, thereby preparing the capacitor packaging material.

[0081] Comparative Example 1

[0082] A reference capacitor packaging material was prepared according to the method of Example 1, except that the same mass of unmodified spherical silica was used instead of the modified spherical silica a-1, and the other conditions were the same as those of Example 1, thereby preparing a reference capacitor packaging material.

[0083] Comparative Example 2

[0084] A reference capacitor packaging material was prepared according to the method of Example 1, except that the same mass of methyltetrahydrophthalic anhydride was used instead of the modified anhydride b-1, and the other conditions were the same as those of Example 1, thereby preparing a reference capacitor packaging material.

[0085] Comparative Example 3

[0086] A reference capacitor packaging material was prepared according to the method of Example 1, except that the adhesive component C was not prepared. The other conditions were the same as those of Example 1, thereby preparing a reference capacitor packaging material including only the resin component A and the curing component B.

[0087] Comparative Example 4

[0088] A reference capacitor packaging material was prepared according to the method of Example 1, except that the same mass of reference spherical silica da-1 was used instead of the modified spherical silica a-1, and the other conditions were the same as those in Example 1, thereby preparing a reference capacitor packaging material.

[0089] Comparative Example 5

[0090] A reference capacitor packaging material was prepared according to the method of Example 1, except that the same mass of reference spherical silica da-2 was used instead of the modified spherical silica a-1, and the other conditions were the same as those in Example 1, thereby preparing a reference capacitor packaging material.

[0091] Test Case

[0092] The capacitor packaging materials prepared in the examples and comparative examples were subjected to performance tests according to the following methods, and the results are shown in Table 1.

[0093] (1) Linear expansion coefficient test: The resin component A and the curing component B of the capacitor packaging material were mixed in a mass ratio of 100:100. After curing at 120°C for 12 hours, the linear expansion coefficient was tested according to the method in GB / T36800.2-2018, and the tensile strength and elongation at break were tested according to the method in GB / T 2567-2021.

[0094] (2) Adhesion test between ceramic interface and packaging material: The surface of the ceramic component is coated with adhesive component C (if there is no adhesive component C, the mixture of resin component A and curing component B is directly coated) and then placed in a mold. The resin component A and curing component B of the capacitor packaging material are mixed in a mass ratio of 100:100, poured into the mold, and cured at 120°C for 12 hours. The cured product is placed in a hot and cold cycle box and subjected to 10 cycles of hot and cold alternation, each cycle lasting 6 hours. The temperature change range is -40°C / 105°C, and the temperature rise and fall rate is 2±0.5°C / min. After the end, the product changes are observed to check whether the epoxy curing layer (formed by the mixed curing of resin component A and curing component B) is cracked and the bonding state between the packaging material and the ceramic component is observed.

[0095] Table 1

[0096]

[0097]

[0098] From the results of Table 1, it can be seen that compared with the comparative example, in the packaging materials provided by Examples 1 to 3, the mixture formed by the resin component A and the curing component B has good fluidity, and the epoxy cured layer after pouring and curing has no cracks or cracks, and is well combined with the ceramic element without gaps. Although the viscosity of the mixture formed by the resin component A and the curing component B in the packaging material provided by Example 4 is slightly increased, the elongation at break is good, and the epoxy cured layer after pouring and curing has fine cracks but no cracks. Compared with the situation where cracks occur, it can still play a protective role for the capacitor. From the comparison results of Example 1 and Comparative Example 1, Comparative Example 4, and Comparative Example 5, it can be seen that the use of modified spherical silica or the use of only a single coupling agent modified spherical silica has little effect on the linear expansion coefficient, but the viscosity of the mixture of the resin component A and the curing component B increases, the fluidity deteriorates, and the elongation at break is significantly reduced, resulting in fine cracks in the epoxy cured layer after pouring and curing. From the comparison results of Example 1 and Comparative Example 2, it can be seen that when the modified anhydride is not added and only the unmodified anhydride is added, the viscosity of the mixture of resin component A and curing component B is low and the elongation at break is significantly reduced, resulting in fine cracks in the epoxy cured layer after pouring and curing. From the comparison results of Example 1 and Comparative Example 3, it can be seen that when the adhesive component C is not used, the epoxy cured layer after pouring and curing the mixture of resin component A and curing component B has no cracks, but there is a small gap between it and the ceramic element.

[0099] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A capacitor packaging material, characterized in that: The capacitor packaging material comprises a resin component A, a curing component B and an adhesive component C; the resin component A contains bisphenol A epoxy resin I, polyether polyol I and optionally a rubber toughening agent I and modified silicon dioxide I; The curing component B contains anhydride and optionally a rubber toughening agent II and modified silica II; The resin component A contains a rubber toughening agent I and / or the curing component B contains a rubber toughening agent II, the resin component A contains modified silicon dioxide I and / or the curing component B contains modified silicon dioxide II; the adhesive component C contains epoxy-modified acrylic resin, bisphenol A epoxy resin II and optional surface additives and diluents; the modified silicon dioxide I and modified silicon dioxide II are obtained by independently using a silane coupling agent and an aluminate coupling agent to modify silicon dioxide; the acid anhydride includes a modified acid anhydride and an optional unmodified acid anhydride; The modified acid anhydride is obtained by esterifying polyether polyol II with unmodified acid anhydride in the presence of a catalyst; the epoxy-modified acrylic resin is obtained by polymerizing acrylic acid, hydroxy acrylate compounds, acrylate compounds and bisphenol A epoxy resin III in the presence of an initiator.

2. The capacitor packaging material according to claim 1, characterized in that: Based on the total mass of the resin component A and the curing component B, the content of the bisphenol A epoxy resin I is 10-20wt%, the content of the polyether polyol I is 0.5-2.5wt%, the content of the acid anhydride is 10-20wt%, the total content of the rubber toughening agent I and the rubber toughening agent II is 1-5wt%, and the total content of the modified silica I and the modified silica II is 50-79wt%.

3. The capacitor packaging material according to claim 1, characterized in that: Based on the total mass of the resin component A, the content of the bisphenol A epoxy resin I is 20-40wt%, the content of the polyether polyol I is 1-5wt%, the content of the rubber toughening agent I is 1-5wt%, and the content of the modified silicon dioxide I is 50-78wt%; Preferably, based on the total mass of the curing component B, the content of the acid anhydride is 20-40wt%, the content of the rubber toughening agent II is 1-5wt%, and the content of the modified silicon dioxide II is 55-79wt%; Preferably, based on the total mass of the adhesive component C, the content of the epoxy-modified acrylic resin is 40-60wt%, the content of the bisphenol A epoxy resin II is 10-30wt%, the content of the surface additive is 0-5wt%, and the content of the diluent is 0-45wt%.

4. The capacitor packaging material according to claim 1, characterized in that: The mass ratio of the resin component A to the curing component B is 100:(80-120); Preferably, the bisphenol A epoxy resin I, bisphenol A epoxy resin II and bisphenol A epoxy resin III are each independently selected from one of E20, E44, E51 and E54; Preferably, the polyether polyol I and the polyether polyol II are each independently selected from at least one of polytetramethylene glycol, polyethylene glycol, polypropylene glycol, polyoxypropylene glycol and polyoxypropylene triol; Preferably, the number average molecular weight of the polyether polyol I and the polyether polyol II is independently 200 to 1000 g / mol; Preferably, the rubber toughening agent I and the rubber toughening agent II are each independently selected from at least one of carboxyl liquid nitrile rubber, hydroxyl-terminated liquid nitrile rubber, polysulfide rubber, liquid silicone rubber, and ABS.

5. The capacitor packaging material according to claim 1, characterized in that: The mass ratio of the silane coupling agent to the aluminate coupling agent is (1-2):1; Preferably, the mass ratio of the sum of the mass of the silane coupling agent and the aluminate coupling agent to the mass of silicon dioxide is (0.02-0.05):1; Preferably, the silicon dioxide is spherical silicon dioxide; Preferably, the modification reaction conditions include: temperature of 100-140° C. and time of 4-6 h.

6. The capacitor packaging material according to claim 1, characterized in that: The mass ratio of the modified anhydride to the unmodified anhydride is 1:(0.3-0.5); Preferably, in the preparation process of the modified acid anhydride, the mass ratio of the polyether polyol II, the unmodified acid anhydride and the catalyst is (1.5-2.5):1:(0.01-0.03); Preferably, the conditions of the esterification reaction include: a temperature of 130 to 160°C; Preferably, the unmodified acid anhydride is selected from at least one of tetrahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, hexahydrophthalic anhydride, methylnadic anhydride, and dodecylsuccinic anhydride; Preferably, the catalyst is selected from at least one of tetrabutylammonium bromide, benzyltriethylammonium chloride, and boron trichloride zinc alkyl tertiary amine.

7. The capacitor packaging material according to claim 1, characterized in that: The preparation method of the epoxy-modified acrylic resin comprises the following steps: subjecting bisphenol A epoxy resin III to a ring-opening addition reaction with acrylic acid, subjecting the obtained intermediate product to a polymerization reaction with a hydroxy acrylate compound and an acrylate compound in the presence of an initiator, and the obtained product is the epoxy-modified acrylic resin; Preferably, the molar ratio of the bisphenol A epoxy resin III to acrylic acid is (1-1.2):1; Preferably, the molar ratio of acrylic acid to hydroxy acrylate compounds and acrylate compounds is 1:(1.5-4):(0.5-1.5); Preferably, the conditions of the ring-opening addition include: temperature of 70 to 90° C., time of 1 to 3 h; Preferably, the polymerization reaction conditions include: temperature of 70 to 90° C., time of 2 to 3 h; Preferably, the hydroxyacrylate compound is selected from at least one of hydroxypropyl acrylate, hydroxypropyl methacrylate, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxybutyl acrylate and hydroxybutyl methacrylate; Preferably, the acrylic acid ester compound is selected from at least one of methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate and butyl methacrylate.

8. The method for preparing a capacitor packaging material according to any one of claims 1 to 7, characterized in that: The preparation method comprises: mixing bisphenol A epoxy resin I, polyether polyol I, and optional rubber toughening agent I and modified silicon dioxide I to obtain resin component A; mixing acid anhydride, optional rubber toughening agent II and modified silicon dioxide II to obtain curing component B; and mixing epoxy-modified acrylic resin, bisphenol A epoxy resin II, and optional surface additives and diluents to obtain bonding component C.

9. Use of the capacitor packaging material according to any one of claims 1 to 7 in capacitor devices requiring packaging.

10. A capacitor packaging method, characterized in that: The capacitor packaging method comprises: coating the adhesive component C of the capacitor packaging material described in any one of claims 1 to 7 on the surface of the capacitor material to form an adhesive layer, and then mixing the resin component A and the curing component B of the capacitor packaging material described in any one of claims 1 to 7 and coating them on the surface of the adhesive layer, and completing the capacitor packaging after curing.

Citation Information

Cited By

  • Epoxy resin composition as well as preparation method and application thereof

    CN120924205A